Real-life results of sofosbuvir based therapy for patients with hepatitis C - Zhivitsa, D. G.; Zhivitsa, L. V.; Shynkarenko, V. L.; Tsaryova, O. V.; Siyanova, L. Yu.; Glazunova, G. V. (Modern medical technology, 2019)
Purpose of the study. The sofosbuvir (SOF) based regimes for the treatment of patients infected with hepatitis C virus (HCV) has improved rates of sustained virological response (SVR) considerably in recent trials. There is only limited data concerning the efficacy and safety in a real-life cohort. We analyzed the treatment outcome of SOF based regimes for chronic hepatitis C patients in a real life setting. Materials and methods. This retrospective study analyzed 205 patients with chronic HCV infection. The following treatments were given according national guidelines: SOF + pegylated interferon alpha-2b + ribavirin for 12 weeks; SOF + ribavirin for 12–24 weeks. Results. Among 3 patients withgenotype 1a HCV the SVR12 rate was 100%, among 100 patients with genotype 1bHCV the SVR12 rate was 92%, among 11 patients with genotype 2 HCV the SVR12 rate was 90.9% and among 91 patients with genotype 3a HCV the SVR 12 rate was 96,7%. Treatment was safe, most of the side effects and laboratory abnormalities (anemia, neutropenia) found during this study were associated with pegylated interferon or ribavirin. Conclusion. In real life setting treatment regimens for chronic hepatitis C patients with SOF based regimens are highly effective and safe, including patients with cirrhosis and treatment experienced patients